2021
DOI: 10.3390/ijms22095050
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Hydrocephalus Following Aneurysmal Subarachnoid Hemorrhage

Abstract: Hydrocephalus is a common complication of aneurysmal subarachnoid hemorrhage (aSAH) and reportedly contributes to poor neurological outcomes. In this review, we summarize the molecular and cellular mechanisms involved in the pathogenesis of hydrocephalus following aSAH and summarize its treatment strategies. Various mechanisms have been implicated for the development of chronic hydrocephalus following aSAH, including alterations in cerebral spinal fluid (CSF) dynamics, obstruction of the arachnoid granulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 133 publications
(175 reference statements)
2
37
0
1
Order By: Relevance
“…Emerging data have established that inflammatory pathways are likely to play an essential role in the pathogenesis of aHCP. Inflammatory markers in CSF and peripheral blood are associated with the possibility of developing aHCP ( 9 , 10 , 12 , 39 ). Lower sPi levels are negatively correlated with the levels of inflammatory cytokines ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging data have established that inflammatory pathways are likely to play an essential role in the pathogenesis of aHCP. Inflammatory markers in CSF and peripheral blood are associated with the possibility of developing aHCP ( 9 , 10 , 12 , 39 ). Lower sPi levels are negatively correlated with the levels of inflammatory cytokines ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysmal subarachnoid hemorrhage (aSAH) is a fast developing, devastating, and life-threatening hemorrhagic stroke with high mortality and disability ( 1 3 ). Hydrocephalus (HCP) is a frequent complication of aSAH, with a reported incidence ranging from 6.5 to 85% ( 4 – 7 ), which is classified as acute (0–3 days post-hemorrhage), subacute (4–13 days post-hemorrhage), or chronic (14 days post-hemorrhage) ( 8 , 9 ). Acute hydrocephalus (aHCP) is a potentially treatable cause of early neurological deterioration, and 20% of aSAH patients develop aHCP within 72 h ( 6 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…ризм ВББ -серед прооперованих ендоваскулярно (9 (40,9 %) Чинниками, що призводять до розвитку хронічної гідроцефалії після аневризматичного САК, вважають різні механізми (зміну ліквородинаміки, обструкцію пахіонових грануляцій продуктами розпаду крові та розвиток спайкового процесу в шлуночковій системі) [5].…”
Section: оригінальні статтіunclassified
“…Attention has been paid to the change in osmotic pressure caused by a large amount of protein accumulation in the CSF, which disrupts the osmotic balance of CSF circulation causing hydrocephalus [36]. Several studies have shown that early CSF drainage plus EVD can reduce the content of erythrocyte degradation products and CSF-TP, thereby reducing the incidence of CSF obstruction and hydrocephalus [37][38][39]. Given that the correlation between CSF-TP and hydrocephalus has been con rmed [40], the present study included CSF-TP as the research object.…”
Section: Pathogenesis Of Phhmentioning
confidence: 99%